Molecular properties of the PCO radical: heat of formation and the isomerization pathways - Viana, Rommel B.; Guimaraes, Amanda R.; Souza, Aguinaldo R. de [UNESP]; Silva, Alberico B. F. da (Springer, 2014)
The potential energy surface of [P,C,O] system in the ground state was investigated by quantum chemical methods. Four different isomers were characterized at the B3LYP/aug-cc-pVTZ: COP (i1), cPCO (i2), PCO (i3), and CPO (i4). The linear species i3 is the global minimum in the ground state surface, while i4 is a bent structure, and i2 is a cyclic isomer. In view to evaluate the bond nature of each isomer, a QTAIM and a NBO analyses were applied. The triangular species presents a ring critical point which confirms its cyclic structure instead of a T-shape one. The stability increases in the following order: i3 > i2 > i1 > i4. The energy gap between i3 and i2 ranges from 49.20 to 51.15 kcal mol(-1). The reaction barrier energies that converge into the direction of i3 showed values around 10 kcal mol(-1), while the reverse barriers are considerably large (62.85 kcal mol(-1)). The i3 heat of formation at 298 K ranges from 11.83 to 19.41 kcal mol(-1).
Keywords: Charge analysis; PCO radical; Natural resonance theory; QTAIM; Renner-Teller; Resonance Weight